The Phenomenon of the Freedom Party: the Effect of Newness or the Beginning of a New Value Cleavage? - Ramonaitė, Ainė (Politologija, 2021)
The article analyzes the reasons of success of the Freedom Party in the 2020 Seimas elections. The case of Freedom Party is particularly interesting as it did not appeal to the median voter like previous new parties, but took a clearly liberal stance on such vulnerable issues (in rather conservative Lithuanian society) as LGBT rights. The article examines several probable accounts of the success story of the party: the newness of the party, the value shift in the society and the realignment of the voters. The article employs the data of the 2020 post-election survey and other relevant data sets. The analysis revealed that the effect of novelty contributed somewhat to the success of the Freedom Party, but the main reason for its good performance was the ability to mobilize liberal-minded voters, the number of which increased significantly compared to the 2016 Seimas elections. The party was able not only to take advantage of the changing values of the new generation, but also to consolidate liberal-minded voters who were previously dispersed. The results of the analysis suggest that attitudes on the conservatism–liberalism dimension have become an important factor determining party preferences in Lithuania, while so far, the only significant cleavage in Lithuania was based on different attitudes towards Russia and the Soviet past.
Keywords: electoral behavior; 2020 Seimas elections; Freedom Party; new parties; political cleavages